Validity and reliability “K² REBT” group counseling module depression among students - Ishak, Nor Asikhin; Ishak, Nurul Huda; Khalid, Mohamad Sukeri (International Journal of Evaluation and Research in Education (IJERE), 2025)
Depression among teenagers, especially students, is an increasing concern with serious consequences, including criminal behavior and suicide. This study develops a rational emotive behavior therapy (REBT) counseling module aimed at reducing irrational beliefs and enhancing the cognitive, emotional, and behavioral well-being of depressed students. The module comprises four sub-modules: self-acceptance, feelings, beliefs, and challenging, based on established REBT principles. The 30 students diagnosed with depression participated in reliability testing, while content validity was assessed by five experts, yielding a high validity quotient of 0.930. The module’s reliability was confirmed with a Cronbach’s alpha of 0.964, indicating strong internal consistency. These findings suggest that the REBT Module is a highly valid and reliable tool for improving coping strategies and alleviating depression among students, making it a valuable addition to school counseling programs.